Improved Line Tracking System for Autonomous Navigation of High-Speed Vehicle - Yahya Zare Khafri; Ali Jahanian (Institute of Advanced Engineering and Science, 2012)
Line tracking navigation is one of the most widely techniques used in the robot navigation. In this paper, a customized line tracking system is proposed for autonomous navigation of high speed vehicles. In the presented system, auxiliary information -in addition to the road path- is added to the tracking lines such as locations of turn and intersections in the real roads. Moreover, the geometric position of line sensors is re-designed enables the high rate sensing with higher reliability. Finally, a light-weight navigation algorithm is proposed allow the high-speed movement using a reasonable processing power. This system is implemented on a MIPS-based embedded processor and experimental results with this embedded system show more than 98% accuracy at 200km/h with a 1GHz processor is viable.DOI: http://dx.doi.org/10.11591/ijra.v1i3.766